Retrospective Analysis of Studies on Differentiated Instruction of English for Specific Purposes - Synekop, Oksana (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article represents the historical analysis of differentiated instruction of English for specific purposes at university level. It also defines the factors contributing to successful use of differentiated instruction in teaching English for Specific Purposes to information technology students of universities.
Keywords: differentiated instruction; English for specific purposes; teaching-learning process; factors of successful English language teaching; information technology students; university